Understanding the position of urban spatial configuration on the feeling of insecurity from crime in public spaces - Widya Putra, Dimas; Salim, Wilmar A.; Indradjati, Petrus Natalivan; Prilandita, Niken (Frontiers in Built Environment, 2023)
Many studies have discussed crime and the feeling of insecurity in the public space. These studies produce diverse findings from various variables and different objects. However, the urban spatial configuration is still left unexplored in the study of insecurity from crime in the public space. The purpose of this study is to discuss the position of urban spatial configuration elements on the feeling of insecurity from crime in the public space evidenced by international literature. This study uses a systematic review method by evaluating studies published between 1970 and 2021. The results of this study state that studies on crime and feeling of insecurity in public spaces in urban planning and urban design context mainly evaluated the design features (crime prevention through environmental design) and Socio-demographics at micro - meso scale in the built environment. In contrast, urban spatial configuration variable or macro scale still underexplored. Studies have shown that issues will occur if policy-making and planning in urban areas ignore individual perceptions of feeling insecure regarding crime at macro scale. This study suggests that more researchers should evaluate the feelings of insecurity from crime in public spaces on a macro scale, namely the urban spatial configuration dimension, including city size, development type, the distribution pattern of population and job, degree of clustering, and landscape connectivity